Pengaruh Pengembangan Karir, Lingkungan Kerja, dan Self Efficacy Terhadap Komitmen Organisasi Pegawai di Dinas Kesehatan Provinsi Kepulauan Riau Dengan Kepuasan Kerja Sebagai Variabel Intervening - Sulistiana, Rita; Yanti, Sri (Zona Manajerial: Program Studi Manajemen (S1), 2022)
This research was conducted with the aim of finding out whether there is a direct influence of career development, work environment, self-efficacy and job satisfaction on organizational commitment, and to find out whether career development, work environment, self-efficacy have a direct effect on employee job satisfaction. The samples from this research were employees who worked at the Riau Islands Provincial Health Service. A total of 75 questionnaires were distributed and all were returned, using a non-probability sampling technique. To analyze this research data using multiple regression analysis techniques using SmartPLS software. Based on the research results, it can be concluded that the variables, career development and job satisfaction have no significant direct effect on employee organizational commitment with a significance level of > 0.05. Meanwhile, the work environment and self-efficacy on employee organizational commitment determine it directly with a significance of <0.05. The research results show that variables, work environment and self-efficacy directly determine job satisfaction with a significance level of <0.05. The results of the indirect influence show that the variables of career development, work environment and self-efficacy on organizational commitment which are mediated by job satisfaction have an insignificant effect, with a significance level of > 0.05. The R Square coefficient of determination for career development, work environment, self-efficacy and job satisfaction on employee performance is 0.858 and career development, work environment, self-efficacy on job satisfaction is 0.865.